SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/113936-ms
|View full text |Cite
|
Sign up to set email alerts
|

ASP Processes: Wide Range of Conditions for Good Recovery

Abstract: Design of an alkaline-surfactant-polymer (ASP) process requires knowledge of the amount of soap formed under alkaline conditions from naphthenic acids in the crude oil. We show here for several crude oils that the acid number determined by nonaqueous phase titration is approximately twice that found by hyamine titration of a highly alkaline aqueous phase used to extract soaps from the crude oil. This acid number by soap extraction should provide a better estimate than nonaqueous phase titration. This soap inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…This formulation reduced oil/water IFT to the order of 10 −3 mN/m and had displaced oil successfully in previous ASP sandpack experiments (Liu et al 2008b). Simulations indicate that high recovery is possible for a wide range of conditions with injection below optimal salinity of the surfactant owing to development of a gradient in soap fraction (Liu et al 2008a).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This formulation reduced oil/water IFT to the order of 10 −3 mN/m and had displaced oil successfully in previous ASP sandpack experiments (Liu et al 2008b). Simulations indicate that high recovery is possible for a wide range of conditions with injection below optimal salinity of the surfactant owing to development of a gradient in soap fraction (Liu et al 2008a).…”
Section: Resultsmentioning
confidence: 75%
“…The optimal salinities for the three crude oils and NI blend are shown in Fig. 2 as a function of the fraction soap/(soap+surfactant), with soap content based on the amount of soap extracted from the crude oil for highly alkaline conditions as measured by aqueous-phase titration (Liu et al 2008a). Arrows in this fi gure show the values of the soap fraction determined from the water/oil ratio corresponding to waterfl ood residual-oil saturation.…”
Section: Resultsmentioning
confidence: 99%
“…13 shows that the soap content by such aqueous extraction is about one-half of the TAN, which is measured by nonaqueous titration. Apparently about one-half of the TAN content is too hydrophobic to be extracted into the aqueous phase (e.g., asphaltene) and/or is too hydrophilic to be detected by hyamine titration (Liu, et al, 2008b). The Salager, et al (1979) mixing rule was found to be followed reasonably well when the aqueous titration method was used to quantify the soap content of the crude oil, Fig.…”
Section: Wor and Surfactant Concentrationmentioning
confidence: 87%
“…If sodium naphthenate is to act as a surfactant, it should partition into the aqueous phase at low electrolyte concentrations and be measurable by hyamine titration for anionic surfactants. It was found (see later) that the sodium naphthenate determined by extraction into the aqueous phase and measured by hyamine titration is about one-half of the TAN value (Liu, et al, 2008b). It is hypothesized that the TAN includes components that are too lipophilic to be extracted to the aqueous phase and/or too hydrophilic to be detected by hyamine titration.…”
Section: Reduced Surfactant Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation